24x+66=-66+27x

Simple and best practice solution for 24x+66=-66+27x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24x+66=-66+27x equation:


Simplifying
24x + 66 = -66 + 27x

Reorder the terms:
66 + 24x = -66 + 27x

Solving
66 + 24x = -66 + 27x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27x' to each side of the equation.
66 + 24x + -27x = -66 + 27x + -27x

Combine like terms: 24x + -27x = -3x
66 + -3x = -66 + 27x + -27x

Combine like terms: 27x + -27x = 0
66 + -3x = -66 + 0
66 + -3x = -66

Add '-66' to each side of the equation.
66 + -66 + -3x = -66 + -66

Combine like terms: 66 + -66 = 0
0 + -3x = -66 + -66
-3x = -66 + -66

Combine like terms: -66 + -66 = -132
-3x = -132

Divide each side by '-3'.
x = 44

Simplifying
x = 44

See similar equations:

| f(2)=7-5 | | 4(3x-2)+27=6x+1 | | 27+x+44=180 | | 400=0.05(x-520) | | 5x-9y=-15 | | -23=4x-6x | | 1.1p+14=16 | | 5(3x-9)-6=5(x-3)+24 | | 2x^2+2x=264 | | -1-2w=-4 | | -3-(-5-2n)-6(1-5n)=9 | | 9+8m=6m-3 | | 2x-9+6x=-3(3+5x) | | [1+3c]-18=-8 | | 9+8m=-3 | | 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 |

Equations solver categories